2010
DOI: 10.1038/jes.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a toxicokinetic and a questionnaire-based approach to assess methylmercury intake in exposed individuals

Abstract: Methylmercury (MeHg) is a neurotoxic contaminant and one of the main sources of exposure in humans is seafood consumption. It is thus of interest to assess precisely MeHg exposure. The objective of this study was to estimate MeHg daily intake in exposed individuals using two different approaches, a food questionnaire and toxicokinetic modeling, and compare the complementary and use of each method. For this purpose, a group of 23 fishermen from northern Quebec provided blood and hair samples and answered a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
2
6
1
Order By: Relevance
“…With respect to Cd, the current dietary intake in male adults was similar to or lower than those recently found for other countries: 11.0 μg/day in France [26], 49 μg/day in Sweden [28], 14.6 μg/day in China [24], and 9.8 μg/day in Belgium [30]. In turn, Hg and MeHg dietary intakes in male adult were similar to those reported by Noisel et al [25] (6.1 μg/day of MeHg), Arnich et al [26] (7.7 μg/day of Hg), or Cheng et al [29] (13.1 and 3.23-23.3 μg/day, respectively) in Canada, France, and Cambodia, respectively. Finally, the Pb dietary intake in Catalan male adults is lower than intakes recently found in other countries, such as France (14.07 μg/day) [26] or China (13.00 μg/day) [31].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…With respect to Cd, the current dietary intake in male adults was similar to or lower than those recently found for other countries: 11.0 μg/day in France [26], 49 μg/day in Sweden [28], 14.6 μg/day in China [24], and 9.8 μg/day in Belgium [30]. In turn, Hg and MeHg dietary intakes in male adult were similar to those reported by Noisel et al [25] (6.1 μg/day of MeHg), Arnich et al [26] (7.7 μg/day of Hg), or Cheng et al [29] (13.1 and 3.23-23.3 μg/day, respectively) in Canada, France, and Cambodia, respectively. Finally, the Pb dietary intake in Catalan male adults is lower than intakes recently found in other countries, such as France (14.07 μg/day) [26] or China (13.00 μg/day) [31].…”
Section: Resultssupporting
confidence: 87%
“…A comparison of the results of the present study with those reported by other authors shows that our data are very similar or even lower than those previously reported [23][24][25][26][27][28][29][30][31]. Thus, As and InAs dietary intakes in male adults in Catalonia are of the same order than those found in various countries, i.e., InAs 3.8 μg/day in Japan [27], As 55 μg/day and InAs 17 μg/day in France [26], or As 285 μg/day in Belgium [23].…”
Section: Resultscontrasting
confidence: 45%
“…By contrast, the mean measured Hg concentration in hair was 0.76 µg g -1 and only 19% of individuals exceeded the level approximately equivalent to the U.S. EPA RfD (Figure 2). Similar overestimates have been observed in earlier studies on Japan, France, Quebec and indigenous populations in Northern Canada (Gosselin et al, 2006;Loranger et al, 2002;Noisel et al, 2011;Sirot et al, 2008). Linear regression of mean measured hair Hg levels against a variety of predictors reveals significant and positive associations with MeHg intake from seafood consumption and age, and a negative association with body weight (Table 3).…”
Section: Hair Mercury Isotope Analysissupporting
confidence: 86%
“…However, many studies find self-reported fish and shellfish consumption can only weakly explain measured variablity in Hg concentrations in hair and blood (Golding et al, 2013;Lincoln et al, 2011;Mahaffey et al, 2004;McDowell et al, 2004). Prior studies of frequent seafood consumers in Japan (Canuel et al, 2006), France (Sirot et al, 2008), Quebec (Loranger et al, 2002;Noisel et al, 2011), and indigenous populations in northern Canada (Gosselin et al, 2006) have all reported extremely low measured concentrations of Hg in hair and blood relative to ingested MeHg and correspondingly modeled internal concentrations (mean 4-14 fold difference). Despite the consistency in these results, such discrepancies are normally attributed to dietary recall bias and imprecision in exposure biomarkers (i.e., integrated signal of MeHg exposure measured in hair) rather than differences in the pharmacokinetics of MeHg metabolism across individuals (Gosselin et al, 2006;Grandjean and Budtz-Jørgensen, 2010;Sirot et al, 2008;Tsuchiya et al, 2008;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was performed by Noisel et al (2011): 23 Canadian fishermen provided hair and blood samples which were analysed for total Hg. The toxicokinetic model of Carrier was used to estimate the underlying MeHg exposures and these results were compared to exposures estimated by questionnaire.…”
Section: Variability and Uncertainties Of Intake Or Body Burden Estimmentioning
confidence: 99%